The Nede Ritual in Mount Sulung Lombok - Saipul Hamdi; Rosiady Husaenie Sayuti; Ari Gunawan; Ihfan Rahmawadi (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2023)
This article aims to examine the practice of the nede rite among the Sasak people of Lombok, West Nusa Tenggara. The Nede ritual is an everyday activity that combines diverse customary traditions, cultures, and Islamic beliefs to pray to God for rain in a kemaliq or sacred spot. Commonly, Muslims recount istisqo prayers to request rain, but in this Sasak Islamic community, they have invented a unique tradition known as the Nede ritual. The extended drought that resulted in crop failure of the community's agricultural products pushed the community to undertake the Nede ceremony. The complexities of Nede ritual practice inspire inquiry into the ritual's history, stages, symbolic meaning, and community engagement. This study employs a qualitative methodology with a phenomenological approach. The data was gathered through observation and in-depth interviews with traditional authorities, religious leaders, and members of local communities. The findings revealed that the nede ritual was first done in the 1970s when the community suffered from a lengthy drought and could not harvest. This extended drought stumped the community until one of the indigenous elders had a dream and received directions from supernatural creatures to execute a rite on a sacred rock on Mount Sulung. The Nede ritual is not only intricate in execution but also rich in meaning at each level. The rite is accompanied by traditional gendang beleq music. Other data indicate that community participation in this ritual is robust, and they have open access to some stages.